Synching and swimming naturally on the side – the translation of hesitation in dubbing - Romero Fresco, Pablo (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The traditional consideration of audiovisual translation (A VT) as con-strained translation has brought about, in the particular case of dubbing, a great deal of research on the different synchronies at play in this type of translation to the detriment of other equally essential issues such as the naturalness of dubbed dialogue. The aim of this study is to analyse the use of hesitation markers in dubbing in order to look precisely at the naturalness of dubbed dialogue while taking into account the audiovisual constraints. This analysis is carried out by comparing the dubbed dialogue (English-Spanish) of a popular American sitcom to the non-translated but prefabricated dialogue of a Spanish sitcom and finally to spontaneous conversation in Spanish. It is suggested that an approach focusing on the specificity of A VT rather than on its constraints enables not only the analysis of naturalness in dubbed dialogue but also the consideration of factors that can be as revealing as the audiovisual constraints, namely audiovisual leeway.